UPAYA PEMERINTAH KABUPATEN KAMPAR DALAM MEWUJUDKAN ZERO PENGANGGURAN TAHUN 2013-2014 - Nurul Huda Mohsin; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was motivated by the government of Kampar regency very aggressively to achieve zero unemployment namely Kampar free from unemployment. But the realization condition after four years running from 2011 to 2014 unchanged improved. The unemployment rate in Kampar regency is still very high and even the highest ranks second in Riau. There are two formulation of the problem in this research is